A-π-D-π-A pyridinium salts: synthesis, crystal structures, two-photon absorption properties and application to biological imaging1. Issue 29 (7th August 2015) - Liu, Zhaodi; Hao, Fuying; Xu, Huajie; Wang, Hui; Wu, Jieying; Tian, Yupeng
<x xml:space="preserve">Abstract</x> The relationship between the two-photon absorption (TPA) properties and the coplanarity of the cations of LI2, L(BPh4)2 and L[Eu(TTA)4]2, was investigated. L[Eu(TTA)4]2 exhibits larger TPA cross-section and can be successful application in TPE microscopy.